PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVA SD NEGERI 83 PEKANBARU - Rokhmatin, Nisfu; ', Zulkifli; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low learning outcomes IPS students, with an average grade 74.83. While the value of minimum completeness criteria (KKM) IPS is 75. Among the students who totaled 36 people only 20 students who reach KKM with 55.56% classical completeness. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS IVA grade students of SD Negeri 83 Pekanbaru by applying the learning model Quantum Teaching. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the average results IVA grade social studies students of SDN 83 to Pekanbaru from a base score of 74.83 UH I, which became 78.88 with an increase of 5.41%. Classical completeness of the base score to UH I ie from 55.55% Being 75% with an increase of 19.455. IPS learning outcome from the base score to UH II is 73.83 into 84.11 with an increase of 12.40%. UH 1 classical completeness is 75% (not complete), the UH 2 91.66% (completed). Teacher activity during the learning process with the application of quantum model of teaching has increased. At the first meeting of the first cycle with the percentage of 70.45% (quite) rising at a meeting of 2 to 77.27% (good) with an increase of 6.82% in the first meeting of the second cycle with the percentage of 88.63% (good) to 97, 72% (excellent) with an increase of 9.09. Activity of students during the learning process with the application of quantum model of teaching has increased. At the first meeting of the first cycle with percentages of 56.81% (less) increased at a meeting of 2 to 75% (good) with an increase of 18.19% in the first meeting of the second cycle with the percentage of 88.63% (excellent) becomes 95.45 % (excellent) with an increase of 6.82%. IVA-class research results in SDN 83 Pekanbaru prove that the application of Quantum Teaching learning model can improve student learning outcomes IPS IVA grade SDN 83 Pekanbaru.Keywords : quantum teaching, the result of IPS